CSR Spending Deviation from Mandate in India: Understanding the reasons for CSR expenditure gap in India (Journal of Advances and Scholarly Researches in Allied Education, 2022)
A clause in the Companies Act of 2013, mandates that companies allocate two percent of theirrevenues to CSR initiatives. The goal of this research is to examine the reasons behind the CSRexpenditure gap in India. The sample consisted of 200 respondents who filled out the survey. The surveyconcluded with a question designed to collect data on the proportion of a company's budget allocated toCSR initiatives. The questionnaire was discussed with experts in this field and their input was utilized torefine. One of the most significant markers of a company's connection with society is its level of (CSR),even though the CSR effect operations cannot always be quantified in terms of financial allocations. Theresults suggest that the inclusion of this provision is a sensible move on the part of regulators aiming toincrease the social responsibility of businesses.